Pengaruh Pendidikan Keluarga, Karakter, Motivasi Terhadap Prestasi Belajar Pendidikan Agama Islam Siswa Kelas VII di SMP Negeri Muara Kati Kecamatan Tiang Pumpung Kepungut Kabupaten Musi Rawas - Seli Junima Sari; Riswanto Riswanto (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
The data collection technique used was aobservation, questionnaire, documentation. The population is 250 and the sample is 63 students. The data analysis techniques used is multiple linear regression, t test and F test. The results research are: the first there is an effect of family education on learning achievement Islamic religious education for class VII students at junior high school Muara Kati Tiang Pumpung Kepungut District, Musi Rawas Regency, tcount > t table (3.164 > 2.00) and a significance level (0.037 <0.05).Secondly there is an influence of character on the learning achievement of Islamic religious education for class VII students at junior high school SMP Negeri Muara Kati Tiang Pumpung Kepungut District Musi Rawas Regency, t count > t table(2.254>2.00) and a significance level (0.047 <0.05).Thirdly there is a motivational effect on the learning achievement of Islamic religious education for class VII students at junior high school Muara Kati Tiang Pumpung Kepungut District Musi Rawas Regency, tcount > t table (2.132 > 2.00) and a significance level (0.049 <0.05).The last there is an influence of family education, character, motivation on learning achievement of Islamic religious education for class VII students at junior high school Muara Kati Tiang Pumpung Kepungut District Musi Rawas Regency which is shown at Fcount > Ftable (1.240 > 3.15) and at a significant level 0.303 <0.05.